The Implementation of ICT School Based in Indonesia: The Benefits and Challenges - Sukristingsih Sukristingsih; Maryanti Etni Mokoagouw (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Nowadays, the concept of learning is becoming modern that linear with the use of information and communication technology (ICT) which is programmed to be involved in all levels of Indonesia education system from Kindergarten to Higher Education. This research is library research that aims to to discuss about the benefits and challenges of ICT school-based implementation in Indonesia. As a country with majority schools located in rural areas, Indonesia has to determine the obstacles endurance and reduce the gab exists. This paper discusses on both sides of the ICT implication which are the benefits and challenges sides. Then, the recommendation is offered for those parties that have close relation to the application of ICT school based can work together to give support.